Selenium and sulfur: mitigation in plant stresses - Lima, Leonardo Warzea [UNESP] (2016)
Plants do not have specific defense mechanisms to counteract the diverse range of abiotic stresses and pollutants into the environment, and its survival depends on the flexibility and adaptability of its own natural defense mechanisms. Furthermore, the maintenance of cellular homeostasis depends on several interlinked and complex mechanisms, while the cellular defense system does not follow a specific pattern of action and may differ due to various factors such as plant species, exposure time to the stress, plant developmental stage, different organs and tissues analyzed. In the light of these considerations, this dissertation aimed to highlight and investigate the role of Sulfur and Selenium against different plant stresses, through the enzymatic and non-enzymatic plant responses and other related defense mechanisms. In the first chapter the author characterize the general biochemical mechanisms of the antioxidant cell defense, specifically the reactive oxygen species (EROs) formation and its chemical singularities and the induced oxidative stress, the enzymatic antioxidant defense system, specifically the superoxide dismutase (SOD) and Catalase (CAT) enzymes, the non-enzymatic mechanisms against the stress, including the Ascorbate-Glutathione cycle, the GSH (reduced glutathione), the phytochelatins and also proline formation. The plant nutritional status during the stress is crucial in order to maintain a proper defense response. In view of this, the chapter two is a published review about the participation of Sulfur (S) on the stress defense. This nutrient has a role in fundamental processes such as electron transport, structure, regulation and it is also associated with photosynthetic oxygen production, abiotic and biotic stress resistance and secondary metabolism. Moreover, few chemical elements are considered benefic to plants, while Selenium (Se) is the most relevant. In the chapter three the author describes the role of Se to detoxify the stress induced by heavy metal contamination, its powerful antioxidant characteristics and the improvement of the antioxidant enzymes activity and overall defense mechanisms. The chapter four consists of a scientific project conducted by the author. The aim of this study was to investigate whether Selenium, under the form of selenite (Na2SeO3), may avoid the uptake, translocation and concentration of Cadmium (CdCl2), in different tomato tissues, indicating possible mechanisms to counteract the stress, as well as to analyze the fruits overall status through the nutritional analyses, dry weight, pigments and proline concentration. The results demonstrate that alleviating effect of Se in tomato under Cd contamination could be related to restriction of Cd2+ uptake and translocation, enhancing micronutrient concentration in fruits and, finally, enhancing fruit proline concentration.